Surfer`s neurapraxia - an uncommon surfing injury of the saphenous nerve - Obana, K. K.; Trofa, D. P.; Ahmad, C. S.; Levine, W. N.; Popkin, C. A. (The Physician and Sportsmedicine, 2024)
Surfer`s neurapraxia is a rare surfing injury of the saphenous nerve secondary to persistent compression of the saphenous nerve along the medial thigh by the surfboard when paddling prone and while sitting upright on the board waiting for a wave. Symptoms may be nonspecific and consist of pain in the medial thigh with or without radiation along the saphenous nerve distribution (medial leg, medial ankle, medial arch of the foot). The saphenous nerve tension test can be utilized to reproduce the symptoms of surfer`s neurapraxia. Treatment consists of conservative management while refractory cases may benefit from injection with local anesthetic. The authors propose the Obana Plan (WATER) for prevention of surfer`s neurapraxia, consisting of Wetsuits, Abduction, Timing, Exercise, and Rest. Overall, surfer`s neurapraxia is a benign condition that can be prevented and managed conservatively.